Anti-Corruption Programs for Governors' Campaign Period 2017-2018 in Java Island - Bramantyo, Muhammad (Universitas Medan Area, 2023)
Most of the studies regarding political campaigns focus heavily on strategy, evaluation, and communication by the candidate during the campaign. However, the study regarding anti-corruption programs campaigned by political candidates is still under research. This study examines the anti-corruption programs proposed by candidates for governor and vice governor on Java Island during 2017-2018 regional election. Further, this study employed a qualitative method using content analysis. The three objectives of this study are to examine the existence of anti-corruption program in vision-mission-working programs (VWMP) set by candidates, communication regarding anti-corruption programs during campaigning, and explanation of anti-corruption programs during electoral debate. The results revealed that only six of the thirteen candidates who ran for regional office included anti-corruption programmes in their VWMPs, seven candidates communicated their programs during the campaign period, and nearly all candidates explained their anti-corruption strategy in the electoral debate because the panelists asked them the question. It is argued that candidates did not prioritize campaigning for their anti-corruption programs because programs such as economic development, free education, and health care are more likely to get sympathy and support from voters